Glycine receptors caught between genome and proteome - functional implications of RNA editing and splicing - Legendre, Pascal; Förstera, Benjamin; Jüttner, Rene; Meier, Jochen C. (Frontiers in Molecular Neuroscience, 2009)
Information processing in the brain requires a delicate balance between excitation and inhibition. Glycine receptors (GlyR) are involved in inhibitory mechanisms mainly at a synaptic level, but potential novel roles for these receptors recently emerged due to the discovery of posttranscriptional processing. GLR transcripts are edited through enzymatic modification of a single nucleotide leading to amino acid substitution within the neurotransmitter binding domain. RNA editing produces gain-of-function receptors well suited for generation and maintenance of tonic inhibition of neuronal excitability. As neuronal activity deprivation in early stages of development or in epileptic tissue is detrimental to neurons and because RNA editing of GlyR is up-regulated in temporal lobe epilepsy patients with a severe course of disease a pathophysiological role of these receptors emerges. This review contains a state-of-the-art discussion of (patho)physiological implications of GlyR RNA editing.